Balancing Growth And Equity: An Evaluation of Foreign Direct Investment Policies in Papua in 2023 - Rheza Auliya Rahman; Markus Anugrah S (Jurnal Administrasi Publik, 2025)
Development that focuses solely on economic growth without considering equity can trigger injustice and worsen inequality. Therefore, it is necessary to implement policies that not only drive economic growth but also ensure a more equitable distribution. This study aims to analyze the level of economic inequality during the 2018–2022 period and to evaluate the design of Foreign Direct Investment (FDI) policies in Papua Province in 2023. The research employs a descriptive quantitative approach, utilizing the Williamson Index to measure the degree of inequality and Input-Output analysis to evaluate FDI policies in Papua. Based on the Williamson Index calculations for the 2018–2022 period, the average level of economic inequality in Papua reached 1.52, which falls into the category of very high inequality. The results of sectoral prioritization mapping through Input-Output analysis indicate that the Electricity and Gas Supply sector, as well as the Information and Communication sector, have output and labor multipliers above the average of all sectors. Thus, these two sectors can serve as strategic focuses in the formulation of investment policies aimed at promoting more inclusive and sustainable economic growth in Papua.